DIELECTRIC SPECIFICS OF THE BLOOD IN UNSTABLE ANGINA: NEW ADDITIONAL TEST FOR ACUTE MYOCARDIAL ISCHEMIA DIAGNOSTICS - Yu. I. Grinshtein; V. G. Sukhovolsky; L. A. Andina; I. Yu. Grinshtein; A. V. Kovalev (Российский кардиологический журнал, 2015)
Aim. To study blood dielectric properties of patients with unstable angina (UA) for the development of novel additional diagnostic criteria for acute myocardial ischemia.Material and methods.   Totally, 61 patient studied with non-ST-elevation acute coronary syndrome (NSTEACS), of those 40 patients having on ECG the changes of ischemic type, 21 patient with ACS without ECG changes. In all patients troponin T was negative in single measurement. Comparison group consisted of the stable angina patients II FC (n=13). Controls consisted of 30 healthy donors of blood transfusion center; to 59% patients with preliminary diagnosis NSTEACS (n=61) diagnostic coronary angiography was don (CAG). To all patients we performed study of dielectric properties of the blood by the Fourier-spectroscopy method.Results.   Dielectric properties of the blood in NSTEACE/UA, during the first hours of pain onset significantly differ from those in stable angina and controls. In 26% of patients dielectric properties of the blood get back later than positive changes of ECG occur (ST return to isoline).Conclusion. Diagnostic test for acute myocardial ischemia, together with ECGdiagnostics and clinical picture makes it possible, in short time, to perform expressdiagnostics of myocardial ischemia when NSTEACS/UA is suspected, especially in comorbidity patients having the same ST depression on ECG, caused by LV hypertrophy.